Ethical Considerations for Phase I Trials in Oncology. Issue 30 (20th October 2022) - Bittlinger, Merlin; Bicer, Selin; Peppercorn, Jeffrey; Kimmelman, Jonathan
Abstract : Phase I trials often represent the first occasion where new cancer strategies are tested in patients. Various developments in cancer biology, methodology, regulation, and medical ethics have altered the ethical landscape of such trials. We provide a narrative review of contemporary ethical challenges in design, conduct, and reporting of phase I cancer trials and outline recommendations for addressing each. We organized our review around four topics, supplementing the first three with scoping reviews: (1) benefit/risk, (2) research biopsies, (3) therapeutic misconception and misestimation, and (4) reporting. The main ethical challenges of conducting phase I trials stem from three issues. First, phase I trials often involve higher research burden and scientific uncertainty compared with other cancer trials. Second, many patients arrive at phase I trials at a transitional point in their illness trajectory where they have exhausted standard survival-extending options. Third, phase I trial results play a major role in informing downstream drug development and regulatory decisions. Together, these issues create distinct pressures for study design, ethical review, informed consent, and reporting. Developments in methodology, regulation, cancer biology, and ethical awareness have helped mitigate some of these challenges, while introducing others. We conclude our review with a series of recommendations regarding trial design, ethical review, consent, and reporting. We also outline several unresolved questions that, if addressed, would strengthen the ethical foundation of phase I cancer trials.